The West Coast Geothermal Province: Insights from Geochemical and Geophysical Exploration for Green Hydrogen Development - Chandrasekharam, Dornadula; Deshmukh, V.; Subba Rao, P.B.V.; Chandrasekharam, D.; Sathishkumar, S.; Srinivas, Y.; Chandrasekhar, V. (Geological Society of India, 2025)
The West Coast Geothermal Province (WCGP), located along India’s western margin, hosts 60 thermal springs with temperatures ranging from 33 to 70°C, classifying it as a low-enthalpy geothermal system. Geochemical analyses suggest that meteoric water percolates through granitic basement rocks, gaining heat from radioactive decay and geothermal gradients. Geophysical investigations have identified shallow geothermal reservoirs and fault/fracture zones that facilitate the upward movement of deep-seated hot water to the surface. Although traditionally overlooked for power generation, low-enthalpy geothermal systems are gaining attention due to technological advancements and the growing demand for sustainable energy solutions such as green hydrogen. Reservoirs with temperatures between 150 to 180°C have the potential to generate 3–5 MWe of off-grid electricity using thermoelectric generators, supporting applications like water desalination and hydrogen production. This study evaluates the potential of WCGP’s low-enthalpy geothermal resources for green hydrogen production, with a focus on both technical and economic aspects. Key technical parameters include reservoir temperature, power generation capacity, and system integration. Economic considerations encompass the Levelized Cost of Energy (LCOE), capital expenditures (CAPEX), operational expenditures (OPEX), and hydrogen production costs. By comparing geothermal hydrogen production with other energy sources, this research assesses its viability and competitiveness within the broader renewable energy landscape. © 2025 Elsevier B.V., All rights reserved.
Keywords: Electricity Generation; Geochemical And Geophysical Studies; Hydrogen Production; Shallow Reservoirs; West Coast Geothermal Province (WCGP)